Evaluación de dos alternativas con recuperación de condensados en el tratamiento de gas natural con respecto al método Joule Thomson (2017)
This project focused on evaluating the recovery of natural gas liquids from two different technologies to that currently implemented by the company (Joule Thomson). The two technologies that were chosen for the project were "Turbo Expander" and "Mechanical Refrigeration", technologies that are used in the gas industry to recover natural gas liquids (NGL) and to adjust the gas temperature for sale according to the norms which require the Single Transport Regulation (RUT). The project begins with a diagnostic of the three alternatives regarding their characterization, products, applications and the advantages and disadvantages of each of them within the gas industry, making a comparison and detailed analysis. Following this from the specifications and conditions coming from the gas treatment plant, theoretical bases and experimental information from other sources, the simulations are performed with the computer program Aspen Hysys 8.4, in order to obtain results of the amount of liquids which is recovered and the conditions under which the plant is managed with each of the technologies. In order to corroborate the information provided by the simulator, the mass transfer balances with Rachford-Rice were performed in each of the separators found in the simulations.